Optimasi Formula Minuman Kopi Kombinasi Ekstrak Jahe (Zingiber officinale) dan Temu Giring (Curcuma heyneana) sebagai Antioksidan - Ika Julianti Tambunan; Ayuning Putri Julian; Kanne Dachi; Siti Muliani Julianty; Sumardi; Samran Samran (Journal of Indah Science and Clinic, 2022)
Coffee contains polyphenols as antioxidant compounds. The content contained in temu giring is a compound of alkaloids, flavonoids, triterpenoids, saponins and tannins as antioxidants. Ginger contains gingerol, beta-carotene, caffeic acid, curcumin as antioxidants. The purpose of this study was to determine whether coffee drink combined with ginger extract (Zingiber officinale) and temu giring extract (Curcuma heyneana) had antioxidant capacity and was favored by volunteers. This research experimentally prepares a coffee drink that combines ginger extract and temu giring extract and demonstrates the discovery of simplicia, the production of ginger extract and temu giring extract, as well as formula optimization using SLD (simplex lattice design) and conducting a survey of respondents on each formula. The yield of ginger simplicia was 500 g and temu giring 750 g with a weight of 88.8 g of ginger extract and 98.2 g of temu giring extract. Determination of formula optimization using SLD is based on the antioxidant activity of the optimal formula, namely the ratio of ginger: temu giring (1/4: 3/4) formula II and the hedonist result of each formula is formula IV with a ratio of ginger: temu giring (3/4). : 1/4).